Pengaruh Model Game Based Learning terhadap Hasil Belajar Matematika Siswa Kelas VIII SMP N 1 Candung Tahun Pelajaran 2025/2026 - Nadia Indriani; Risnawita; Aniswita; Ulva Rahmi (Lembaga Yasin AlSys, 2026)
Mathematics learning outcomes remain a concern because teacher-centered instruction can limit students’ active participation and conceptual understanding. Although the effectiveness of Game-Based Learning in improving learning outcomes has been demonstrated in various studies, research specifically applying this model through an adaptation of Clash of Champions in junior high school mathematics learning remains limited. This study aimed to analyze the effect of a Clash of Champions adaptation-based Game-Based Learning model on the mathematics learning outcomes of eighth-grade students at SMPN 1 Candung in the 2025/2026 academic year. The study employed a quantitative approach with a pre-experimental design. The research sample consisted of an experimental class and a control class selected through purposive sampling. Data were collected using a learning outcomes test and analyzed using descriptive statistics, normality tests, homogeneity tests, and a t-test. The results showed that the mean learning outcome score of students in the experimental class was 72.93, which was higher than the control class mean of 61.37. The hypothesis test results indicated a significant difference between the learning outcomes of the two groups, demonstrating that the implementation of the Clash of Champions adaptation-based Game-Based Learning model had a positive effect on students’ mathematics learning outcomes. These findings strengthen the application of constructivist theory in mathematics learning and emphasize the importance of active, interactive, and student-centered learning experiences. In practical terms, the results can serve as a reference for teachers in implementing innovative learning models to improve mathematics learning outcomes. Future research should examine the effectiveness of this model across more diverse subject matter, educational levels, and learning variables.